2015
DOI: 10.1016/j.chieco.2015.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Long work hours and health in China

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 43 publications
1
17
1
Order By: Relevance
“…In this study, the prevalence of long working hours among participants was 69.3%, which was slightly higher than that (62.0%) of one previous study using Chinese national data from 1991 and 2009 [2], indicating that employees in Shanghai are more prone to working overtime due to the fast-pace life of this megacity. We also found that nearly one-fifth of respondents had depression, and approximately one-fourth showed PMWB.…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations
“…In this study, the prevalence of long working hours among participants was 69.3%, which was slightly higher than that (62.0%) of one previous study using Chinese national data from 1991 and 2009 [2], indicating that employees in Shanghai are more prone to working overtime due to the fast-pace life of this megacity. We also found that nearly one-fifth of respondents had depression, and approximately one-fourth showed PMWB.…”
Section: Discussioncontrasting
confidence: 83%
“…Participants answered the question "How many hours do you currently work on average per week?" Long working hours (defined as overtime per week beyond normal or regular working hours) was operationally defined as more than 40 h/week in this study, which was in line with the definition adopted by many countries, according to a recent International Labor Office survey and previous studies [2,12,19,25]. Then weekly working hours (WWH) were split into four groups (≤40 h, 40 h < WWH ≤ 50 h, 50 h < WWH ≤ 60 h, and >60 h), with ≤40 h used as the reference category.…”
Section: Exposure and Other Variablesmentioning
confidence: 93%
See 1 more Smart Citation
“…The premium for overtime is an important part of the salary, and the employees have to work overtime for additional premiums as well as the basic compensation [26]. For another, Chinese employers are more likely to overburden their employees [27], and working overtime has to be a necessary routine to meet the employer's claims or expectation. Thus, the longer commuters in China are less likely to show shrinking behaviors not only due to the financial reasons, but also owing to the requirement by employers.…”
Section: Discussionmentioning
confidence: 99%
“…The premium for overtime is an important part of the salary, and the employees have to work overtime for additional premiums as well as the basic compensation [26]. For another, Chinese employers are more likely to overburden their employees [27], and working overtime has to be a necessary routine to meet the employer's claims or expectation. Thus, the longer commuters in China are less likely to show shrinking behaviors not only due to the nancial reasons, but also owing to the requirement by employers.…”
Section: Discussionmentioning
confidence: 99%